Strategic Planning Competences for Charter Schools Leaders in Saudi Arabia - Alkhwaiter, Arwa Mohammad Abdulla; Alkhwaiter, Khwater Mohammad Abdulla (Journal of Educational and Psychological Sciences, 2023)
This study aimed to shed light on the competencies of strategic planning for independent school principals. The researchers used the descriptive (theoretical) approach by analyzing the educational literature related to the variables of the study, namely the competencies of strategic planning and school administration. This is by referring to the literature that dealt with the competencies of the school leader, the independent schools, and the competencies of strategic planning as sources of derivation. The list of strategic planning competencies for independent school principals has been built within four main axes: strategic thinking, strategic planning, implementation of the strategic plan, evaluation and follow-up. Each axis includes two areas: cognitive competencies, which are the minimum strategic planning knowledge and skills that must be available to the independent school leader, and performance competencies, which are the minimum strategic planning practices that must be available to the school leader. Comparing the variables of public schools and independent schools.